2017
DOI: 10.4048/jbc.2017.20.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Core Needle Biopsy and Surgical Specimens in Determining Intrinsic Biological Subtypes of Breast Cancer with Immunohistochemistry

Abstract: PurposeWe evaluated the concordance between core needle biopsy (CNB) and surgical specimens on examining intrinsic biological subtypes and receptor status, and determined the accuracy of CNB as a basic diagnostic method.MethodsWe analyzed breast cancer patients with paired CNB and surgical specimen samples during 2014. We used monoclonal antibodies for nuclear staining, and estrogen receptor (ER) and progesterone receptor (PR) status evaluation. A positive test was defined as staining greater than or equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 29 publications
(38 reference statements)
6
44
3
Order By: Relevance
“…Identifying HER2-positive breast cancer patients by CNB is important, as neoadjuvant HER2-targeted therapy is an effective option for these patients. In this study, the CR for HER2 status, as determined by HER2 IHC or reflex HER2 SISH, was as high as 99.7% (kappa, 0.988), which was higher than most previous reports (ranging from 61%-97.3%) [10,[18][19][20][21][22][23][24][25][26][27][28][29]. The reason for this high CR could partially be due to performing reflex HER2 SISH for all HER2 IHC equivocal cases to determine final HER2 status strictly following ASCO/CAP guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…Identifying HER2-positive breast cancer patients by CNB is important, as neoadjuvant HER2-targeted therapy is an effective option for these patients. In this study, the CR for HER2 status, as determined by HER2 IHC or reflex HER2 SISH, was as high as 99.7% (kappa, 0.988), which was higher than most previous reports (ranging from 61%-97.3%) [10,[18][19][20][21][22][23][24][25][26][27][28][29]. The reason for this high CR could partially be due to performing reflex HER2 SISH for all HER2 IHC equivocal cases to determine final HER2 status strictly following ASCO/CAP guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…You et al reported concordance rates as high as 83.5% ( κ = 0.647) for Ki67, probably because Ki67 index had been assessed using 10% intervals instead of a continuous percentage (20% cutoff for high proliferation). Furthermore, they reported a HER2 IHC concordance of 84.8% ( κ = 0.684) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their development was limited by a lack of genetic information obtained prior to treatment. To overcome this limitation, studies have been conducted to confirm a satisfactory level of correlation between results obtained from needle biopsy tissue and surgical specimens [15, 1921].…”
Section: Discussionmentioning
confidence: 99%
“…However, since multigene kits are usually developed with surgical specimens, and commercial multigene tests have not been extensively studied with needle biopsy samples, they are not comprehensively validated for such use [1618]. Even if the core needle biopsy (CNB) shows highly accurate results in determining estrogen receptor (ER), progesterone receptor (PR), and HER2 status [1921], there is a degree of uncertainty in predicting prognosis using multigene test kits with needle biopsy samples prior to initial treatment.…”
Section: Introductionmentioning
confidence: 99%